2022
DOI: 10.1128/spectrum.01860-21
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein Member 8 (HSPA8) Is Involved in Porcine Reproductive and Respiratory Syndrome Virus Attachment and Internalization

Abstract: PRRSV has caused huge economic losses to the pork industry around the world. Currently, safe and effective strategies are still urgently required to prevent and control PRRSV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…HSC70 plays multifunctional roles in viral infection, such as viral entry, intracellular trafficking, and genome replication. 19,22 It is abundant in the cytosol under normal conditions but can translocate to the nucleus under stress, such as heat shock. 48 domains to promote lytic infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSC70 plays multifunctional roles in viral infection, such as viral entry, intracellular trafficking, and genome replication. 19,22 It is abundant in the cytosol under normal conditions but can translocate to the nucleus under stress, such as heat shock. 48 domains to promote lytic infection.…”
Section: Discussionmentioning
confidence: 99%
“…19 HSC70 has been shown to participate in the entry of PRRSV, Dengue virus, and rotavirus. [20][21][22] HSC70 is also involved in viral intracellular trafficking. It mediates the endoplasmic reticulum-to-cytosol transport of Simian virus 40.…”
mentioning
confidence: 99%
“…In this year, our group identified that HSPA8, a housekeeping chaperone, interacts with PRRSV GP4, and is involved in PRRSV attachment and internalization for the first time. Anti-HSPA8 polyclonal antibodies, inhibitors, and the recombinant soluble HSPA8 protein inhibit PRRSV infection in vitro ( Wang et al, 2022 ).…”
Section: Newly Identified Host Cellular Factorsmentioning
confidence: 99%
“…In addition to attachment and entry, HS and vimentin are shown to participate in other stages of PRRSV replication cycle ( Song et al, 2016 ; Guo et al, 2017a ; Chang et al, 2018 ; Zheng et al, 2021 ). Moreover, several novel host cellular factors are identified to be involved in PRRSV attachment and entry, such as non-muscle myosin heavy chain 9 (MYH9) ( Gao et al, 2016 ), syndecan-4 ( Wang et al, 2016a ), epidermal growth factor receptor (EGFR) ( Wang et al, 2016b ), T-cell immunoglobulin and mucin domain (TIM)-1/4 ( Wei et al, 2020 ), and heat shock protein member 8 (HSPA8) ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome virus (PRRSV), a single-stranded positive-strand RNA virus belonging to the Arteriviridae family, causes respiratory disease in piglets and adult swine and late abortions and stillbirths in sows ( 1 , 2 ). As a very successful virus, PRRSV has devastated the swine industry worldwide over 30 years and has shown no sign of slowing down ( 3 , 4 ). Although many commercial vaccines against PRRSV have been made available, unfortunately, neither traditional control strategies nor conventional vaccines provide sustainable control of PRRSV ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%